Pengaruh Kurs,Suku Bunga dan Inflasi Terhadap Return Saham Pada Perusahaan Consumer Good di BEI - Sepriana; Simanjuntak, Jontro (LPPM Universitas Putera Batam, 2022)
In this growing era, people do not only invest through savings, but many try to put their source of funds into stock investments on the Indonesia Stock Exchange. in BEI. The method that researchers use is a quantitative method. The population is consumer goods companies listed on the Indonesia Stock Exchange as many as 19 companies. The data collection technique uses the time series method and the data analysis technique uses multiple linear analysis which is assisted by a data processing tool, namely SPSS version 26. The results show that the exchange rate has a negative and significant effect on stock returns, interest rates have a positive and insignificant effect on stock returns. , Inflation has a positive and insignificant effect on stock returns. Simultaneously exchange rates, interest rates and inflation have a significant effect on stock returns. The result of the coefficient of determination (R2) is 11% and the remaining 89% is influenced by other factors not examined in this study.